Impact of residue retention and nutrient management on carbon sequestration, soil biological properties, and yield in multi-ratoon sugarcane - Pradhan, Aliza; Wakchaure, Goraksha C.; Shid, Dhanashri; Minhas, Paramjit S.; Biswas, Ashis K.; Reddy, Kotha Sammi (Frontiers in Sustainable Food Systems, 2023)
Sequestration of carbon in arable cropping systems is considered as one of the potential climate change mitigation strategies. In this context assessing the potential of sugarcane cropping systems should be a priority, as it leaves substantial amounts of recyclable residues essential for maintaining soil organic carbon (SOC), improving soil health and overall resource enhancement. We evaluated impacts of residue retention and nutrient management practices on the SOC, its pools, storage, soil biology, and yield in a multi-ratooning sugarcane system. A field experiment was conducted in split plot design with residue burning (RB) and residue retention (RR) as main plot treatments and three nutrient management practices i.e. 25% of recommended dose of fertilizers (RDF i.e. 300: 150: 150 kg N, P2O5 and K2O kg ha-1 ) as basal + 75% through fertigation (N1); 50% of RDF as basal + 50% through fertigation (N2) and 75% of RDF as basal + 25% through fertigation (N3) as sub plot treatments in ratoon sugarcane. Soil samples were collected initially and after six years of multi-ratooning (one plant and four ratoon crops) from 0-30 cm soil layer. Results indicated that plots with RR had 21% higher total SOC with 42, 47, 17 and 13% higher very labile, labile, less labile and non-labile C pools, respectively than RB plots (P < 0.05). RR also had higher lability and recalcitrant index than RB. Of the total SOC stock, contribution of passive pools were higher (72-75%) than active pools. Significantly higher dehydrogenase activity (DHA) (86%), alkaline phosphatase activity (APA) (16%) and ß-glucosidase activity (BGA) (22%) were observed in RR as compared to RB plots; whereas for nutrient management practices, it followed the order: N2>N3>N1, respectively. Microbial counts also followed the same trend as that of enzyme activities. Residue retention practices reported higher C sequestration (0.68 Mg C ha-1 yr-1 ), carbon retention efficiency (37%) and yield (38%) with a potential to reduce GHG emission by 2.72 Mg CO2 ha-1 yr-1 as compared to traditional practice. Residue retention and 50-75% RDF as basal is recommended for higher soil C retention and soil biology for sustained sugarcane productivity.